Clinical analysis of uterine intravenous leiomyomatosis: A retrospective study of 260 cases. Issue 12 (15th September 2021) - Peng, Jing; Zhong, Fangfang; Zhu, Yuemeng; Zhang, Mingxing; Zhang, Meng; Lu, Chong; Wang, Yumeng; Qi, Xingling; Wang, Congwen; Li, Guiling
Abstract: Methods: We collected the clinical data of 260 patients admitted to the hospital from April 2003 to September 2019 with pathologically confirmed intravenous leiomyomatosis (IVL) and followed up with these patients regularly. Univariate and multivariate logistic regression analyses were carried out on the relevant recurrence factors. Results: A total of 166 patients were regularly followed up, the median follow‐up time was 36 (range 2–168) months, 14 (5.4%) patients eventually relapsed, and the median recurrence time was 8.5 (range 2–42) months. The univariate analysis showed that age ( p = 0.003) and surgical type ( p < 0.001) were associated with recurrence, and multivariate regression analysis demonstrated that surgical type was the only factor associated with recurrence ( p < 0.001, OR 20.01). Conclusions: The use of gonadotrophin releasing hormone agonist (GnRHa) cannot reduce the postsurgical recurrence rate of patients with UIVL. Compared to total hysterectomy and bilateral salpingo‐oophorectomy (TH‐BSO), total hysterectomy (TH) does not increase the odds of recurrence, but the chance of recurrence with tumorectomy (TE) is 20 times higher than that of TH‐BSO.